New Flavonoid Derivatives from Melodorum fruticosum and Their α-Glucosidase Inhibitory and Cytotoxic Activities - Lien T. M. Do; Jirapast Sichaem (Molecules, 2022)
Three new flavonoid derivatives, melodorones A–C (1–3), together with four known compounds, tectochrysin (4), chrysin (5), onysilin (6), and pinocembrin (7), were isolated from the stem bark of Melodorum fruticosum. Their structures were determined on the basis of extensive spectroscopic methods, including NMR and HRESIMS, and by comparison with the literature. Compounds 1–7 were evaluated for their in vitro α-glucosidase inhibition and cytotoxicity against KB, Hep G2, and MCF7 cell lines. Among them, compound 1 exhibited the best activity against α-glucosidase and was superior to the positive control with an IC50 value of 2.59 μM. On the other hand, compound 1 showed moderate cytotoxicity toward KB, Hep G2, and MCF7 cell lines with the IC50 values of 23.5, 19.8, and 23.7 μM, respectively. These findings provided new evidence that the stem bark of M. fruticosum is a source of bioactive flavonoid derivatives that are highly valuable for medicinal development.